Cognitive exploration strategies and collective decision-making in entrepreneurial business modelling - Tassilo Henike; Katharina Hölzle (Journal of Business Models (JOBM), 2019)
Our Business Model (BM) teaching approach helps students to understand three essential dimensions of cognitive exploration strategies and to experience negotiation strategies in groups for designing a first BM. Didactically, it follows Kolb's Experiential Learning Cycle, including individual paper and case study preparations as well as collective discussions and decision-making.
Keywords: 650; cognition; exploration strategies; entrepreneurial business modelling